Affirm Holdings: supervised machine learning and market disruption - Lopez-Lira, Alejandro (Henry Stewart Talks, 2024)
This case study of Affirm Holdings, a now successful fintech company, describes its use of machine learning to disrupt the market, accomplishing its objective of providing lending opportunities to clients lacking access to traditional credit markets.